Commodity risk assessment of Acer spp. plants from New Zealand. (20th May 2020) - ,; Bragard, Claude; Dehnen‐Schmutz, Katharina; Di Serio, Francesco; Jacques, Marie‐Agnès; Jaques Miret, Josep Anton; Justesen, Annemarie Fejer; MacLeod, Alan; Magnusson, Christer Sven; Milonas, Panagiotis; Navas‐Cortes, Juan A; Parnell, Stephen; et al.
Abstract: The European Commission requested the EFSA Panel on Plant Health to prepare and deliver risk assessments for commodities listed in Commission Implementing Regulation (EU) 2018/2019 as 'High risk plants, plant products and other objects'. This Scientific Opinion covers all plant health risks posed by dormant and free of leaves, 1‐ to 3‐year‐old bare root plants for planting of Acer spp. imported from New Zealand, taking into account the available scientific information, including the technical information provided by New Zealand. The relevance of an EU‐quarantine pest for this opinion was based on evidence that: (i) the pest is present in New Zealand; (ii) Acer spp. are hosts of the pest and (iii) the pest can be associated with the commodity. The relevance for this opinion of any other pest, not regulated in the EU, was based on evidence that: (i) the pest is present in New Zealand; (ii) the pest is absent from the EU; (iii) Acer spp. are hosts of the pest; (iv) the pest can be associated with the commodity and (v) the pest may have an impact and can pose a potential risk for the EU territory. Four pests ( Eotetranychus sexmaculatus, Meloidogyne fallax, Oemona hirta and Platypus apicalis ) that fulfilled all relevant criteria were selected for further evaluation. For the selected pests, the risk mitigation measures proposed in the technical dossier from New Zealand were evaluated taking into account the possible limiting factors. For the selected pests, an expert judgement is given on the likelihood of pest freedom taking into consideration the risk mitigation measures acting on the pest, including uncertainties associated with the assessment. Based on the outcome of Expert Knowledge Elicitation, the degree of pest freedom varies among the pests evaluated. The mite, Eotetranychus sexmaculatus, was the pest most likely to cause plants to fail pest freedom status. The Panel is 95% sure that at least 9, 240 plants per 10, 000 will be free from E. sexmaculatus .